Selected letters of Walt Whitman - Whitman, Walt, 1819-1892 (Iowa Whitman series., 1990)
There has never been an edition of the selected letters of Walt Whitman, a remarkable fact considering how accustomed we are to becoming acquainted with major writers through their letters. Now Edwin Haviland Miller, editor of the six-volume collected writings of Whitman, has used his intimate knowledge of the "good gray poet's" correspondence to produce this revealing selection of 250 letters, introduced and annotated concisely and evocatively. Whitman in these letters is simple, direct, colloquial, adding a counterpoint to his artistic voice and persona as a poet.